2017
DOI: 10.1111/jfpp.13224
|View full text |Cite
|
Sign up to set email alerts
|

Changes of protein composition and its relevance with textural properties during processing of fermented solid beef

Abstract: In this paper, fermented solid beef inoculated with two starter cultures (Lactobacillus curvatus and Pediococcus pentosaceus) in different inoculums concentration, fermentation time, and fermentation temperature was evaluated for change of protein composition (water‐soluble proteins, insoluble protein, and salt‐soluble proteins) and nonprotein nitrogen during fermentation and the relevance with textural properties was also investigated. The amount of water‐soluble and salt‐soluble proteins decreased while nonp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…This research showed that addition of bamboo shoot with different preparation method on fermentation process without adding culture starter of beef meat contributes in change total protein value after fermentation. This phenomenon similar with Zhou et al (2017), studied on fermentation of solid beef inoculated with two starter cultures (Lactobacillus curvatus and Pediococcus pentosaceus) in different inoculums concentration, fermentation time and fermentation temperature. An increase of inoculums concentration, fermentation times and fermentation temperatures could decrease protein composition in term water-soluble protein and salt soluble protein after fermentation, while insoluble protein increased.…”
Section: Chemical Characteristicssupporting
confidence: 73%
“…This research showed that addition of bamboo shoot with different preparation method on fermentation process without adding culture starter of beef meat contributes in change total protein value after fermentation. This phenomenon similar with Zhou et al (2017), studied on fermentation of solid beef inoculated with two starter cultures (Lactobacillus curvatus and Pediococcus pentosaceus) in different inoculums concentration, fermentation time and fermentation temperature. An increase of inoculums concentration, fermentation times and fermentation temperatures could decrease protein composition in term water-soluble protein and salt soluble protein after fermentation, while insoluble protein increased.…”
Section: Chemical Characteristicssupporting
confidence: 73%
“…Meanwhile, free amino acids will undergo decarboxylation, deamination, and Maillard reaction with reducing sugar to decrease their contents ( Poulsen et al., 2013 ). It has been found that polypeptides were produced by proteinase acting on proteins and then were further decomposed into amino acid by the peptidase ( Zhou et al., 2017 ). However, the action of alkali inside the preserved egg can inhibit the activity of protease or peptidase, which indirectly affects the content of amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…The lactic acid bacteria (LAB) and coagulase‐negative Staphylococci (CNS) isolated from the endogenous microbes in traditionally fermented meat products are the most commonly used mixed starters (Bis‐Souza et al ., 2020). LAB can reduce pH and prevent the growth of pathogenic and spoilage microorganisms by rapidly producing lactic acid and bacteriocins to improve safety, stability, and shelf life of products, and to provide an acidic environment for protein degradation and bioactive peptide production (Candogan et al ., 2009; Zhou et al ., 2016). CNS help the production of nitrosomyoglobin and make the product form a stable colour because of its nitrate reductase activity (Cachaldora et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%